2013
DOI: 10.2147/cia.s40438
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic abilities of different calculation formulas for the glomerular filtration rate in elderly Chinese patients with coronary artery disease

Abstract: ObjectiveAs a standard indicator of renal function, the glomerular filtration rate (GFR) is vital for the prognostic analysis of elderly patients with coronary artery disease (CAD). Thus, the search for the calculation equation of GFR with the best prognostic ability is an important task. The most commonly used Modification of Diet in Renal Disease (MDRD) equation and the Chinese version (CMDRD) of the MDRD equation has many shortcomings. The newly developed Mayo Clinic quadratic (Mayo) and Chronic Kidney Dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
3
9
0
3
Order By: Relevance
“…In another study, the reclassification of patients to a better GFR category using the CKD-EPI equation, compared with the MDRD equation, was related to reduction in all-cause mortality. [19] This type of reclassification was also observed in the present study.…”
Section: Is There a Relationship Between Slow Coronary Flow And Normasupporting
confidence: 89%
See 2 more Smart Citations
“…In another study, the reclassification of patients to a better GFR category using the CKD-EPI equation, compared with the MDRD equation, was related to reduction in all-cause mortality. [19] This type of reclassification was also observed in the present study.…”
Section: Is There a Relationship Between Slow Coronary Flow And Normasupporting
confidence: 89%
“…In addition, it was determined that this equation overcame the limitation of the MDRD equation (i.e., the underestimation of GFR at given range). [17][18][19][20] Stevens LA et al [20] showed that bias was substantially decreased with the CKD-EPI equation, compared to measured GFR, particularly among people with eGFR greater than 60 ml/min/1.73 m 2 . The study also found that bias was increased using the MDRD equation, when eGFR was greater than 90 ml/min/1.73 m 2 .…”
Section: Is There a Relationship Between Slow Coronary Flow And Normamentioning
confidence: 99%
See 1 more Smart Citation
“…9 A boa correlação entre a MDRD e a CKD-EPI havia sido verificada anteriormente em pacientes com SCA. 18,19 Provavelmente a alta correlação das últimas ocorra por utilizarem as mesmas variáveis para o cálculo, além do desenvolvimento a partir do mesmo padrão-ouro. 6,7 Já a CG adota a idade e a massa corporal, diferente das demais fórmulas, e foi derivada de estudo utilizando a urina de 24 horas.…”
Section: Discussionunclassified
“…18 O oposto foi verificado por AlFaleh et al, 25 com as mesmas fórmulas. Fu et al, 19 analisando uma população com média de 86 anos, SCA e segmento de mais de 400 dias, mostrou superioridade da CKD-EPI. Já Barra et al, 26 incluindo uma população com idade média de 66 anos, encontraram melhor ASC para MDRD em relação à CG tanto para mortalidade, quanto para readmissão por insuficiência cardíaca descompensada num segmento de dois anos.…”
Section: Discussionunclassified